2015
DOI: 10.1038/srep12047
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes and Proton Transfer in Cytochrome c Oxidase

Abstract: In cytochrome c oxidase electron transfer from cytochrome c to O2 is linked to transmembrane proton pumping, which contributes to maintaining a proton electrochemical gradient across the membrane. The mechanism by which cytochrome c oxidase couples the exergonic electron transfer to the endergonic proton translocation is not known, but it presumably involves local structural changes that control the alternating proton access to the two sides of the membrane. Such redox-induced structural changes have been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…However, its dissociation from the hydroxyethylfarnesyl group does not induce the postulated bridging of the gap between His413 and Ser461 with additional waters. Indeed, the same type of structural change of the equivalent serine has been observed in R. sphaeroides CcO, where an H channel is not operative (33), and in which recent kinetic data on wild-type and a Ser425Ala mutant show no major differences in their reaction kinetics or coupling efficiencies (50). It is not conserved in the structurally and biochemically wellcharacterized B-type oxidase from Thermus thermophilus, the quinol oxidase from Escherichia coli, and various C-type oxidases (57).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, its dissociation from the hydroxyethylfarnesyl group does not induce the postulated bridging of the gap between His413 and Ser461 with additional waters. Indeed, the same type of structural change of the equivalent serine has been observed in R. sphaeroides CcO, where an H channel is not operative (33), and in which recent kinetic data on wild-type and a Ser425Ala mutant show no major differences in their reaction kinetics or coupling efficiencies (50). It is not conserved in the structurally and biochemically wellcharacterized B-type oxidase from Thermus thermophilus, the quinol oxidase from Escherichia coli, and various C-type oxidases (57).…”
Section: Discussionmentioning
confidence: 55%
“…These findings agree with observations in R. sphaeroides CcO (33), where the same type of structural change of the equivalent serine has been observed. In this enzyme, the H channel is not operative, and recent kinetic data on wild-type and a Ser425Ala mutant show no major differences in their reaction kinetics or coupling efficiencies (50). A low pK a of His413 is in accord with a location that is surrounded by hydrophobic residues (SI Appendix, Fig.…”
Section: Model System Cu a Heme A Bnc His413 Asp51 Glu242 Tyr244 Lys3mentioning
confidence: 82%
“…It would also be interesting to address the role of the Rcf proteins in controlling the ratio of O 2 reduction over ATP formation (the P/O ratio) because changes in structure, such as those changes presumably induced by removal of Rcf1, may interfere with proton pumping (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…To interrogate the effect of S425 in RsCcO (equivalent to S382 in bCcO) on proton translocation in the D pathway, Brzezinski and coworkers (42) mutated S425 to alanine and measured its proton translocation efficiency during the O 2 reaction cycle as a function of pH. They found that structural changes in S425 propagate to the D pathway, thereby modulating proton transfer rates (42). These data suggest that the S382-linked allosteric structural transition may play a role in proton translocation in both mammalian and bacterial oxidases.…”
Section: Discussionmentioning
confidence: 99%